Edukasi Ktr Dan Ispa Pada Masyarakat Di RT 09 Wilayah Kerja Pkm Jalan Gedang Kota Bengkulu - Destiana, Yenni; Haryanto, Adi; Santiwulansari, Santiwulansari; Cempaka, Febri Melati; Esrawati, Esrawati; Anissa, Kintan; Hilinti, Yatri (Jurnal Dehasen Untuk Negeri, 2026)
Acute Respiratory Infection (ARI) is one of the leading causes of morbidity and mortality, especially among toddlers and children. The community in RT 09, Jalan Gedang PKM working area, Bengkulu City faces high incidences of cough and respiratory infections due to unhealthy behaviors and unclean environments. This community service aims to provide health education regarding the prevention of cough and respiratory infections to the local community. The methods employed include interactive counseling, demonstrations of clean living practices, and dissemination of educational media such as leaflets and posters. The 2025 Thematic Community Service Program (KKN-T) of Universitas Dehasen Bengkulu focuses on ARI prevention through an educational approach, namely ARI counseling, implementation of Smoke-Free Areas (SFA), and distribution of leaflets and digital education. This activity is conducted in collaboration with village authorities and the local community. The results indicate increased public awareness regarding the importance of environmental cleanliness and reduction of exposure to cigarette smoke, aiming to improve lung capacity and reduce the risk of respiratory infection symptoms. The program has proven effective as a community-based promotive and preventive strategy that can serve as a model for other regions. Cross-sector collaboration and continuous education are essential to support efforts to reduce ARI incidence, as well as contribute to stunting prevention by improving children’s respiratory health.